2019
DOI: 10.1002/biof.1602
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Long noncoding RNA Mirt2 prohibits lipopolysaccharide‐evoked HK‐2 cell injury via modulation of microRNA‐126

Abstract: Long noncoding RNA myocardial infarction‐associated transcript 2 (lncRNA Mirt2) is a burgeoning lncRNA, its anti‐inflammatory capacity has been testified. Nonetheless, the functions of Mirt2 in immunoglobulin A nephropathy are unexplored. We tried to impart the influences of Mirt2 in lipopolysaccharide (LPS)‐evoked HK‐2 cells damage. HK‐2 cells were manipulated with 10 ng/ml LPS, next cell viability, apoptosis, reactive oxygen species (ROS) generation, pro‐inflammatory factors and Mirt2 expression were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Nuclear factor erythroid-related factor 2 (NRF2) is a redox-sensitive transcription factor that prevents oxidative stress by regulating cytoprotective genes, including NAD(P)H quinone dehydrogenase 1 (NQO1), heme oxygenase 1 (HO-1) and glutamate-cysteine ligase [ 14 ]. It is worth noting that it is reported that after feeding a high-fat diet, NRF2 inhibits lipid accumulation and oxidative stress in the liver tissue of mice by inhibiting lipogenesis and cholesterol production signaling pathways [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor erythroid-related factor 2 (NRF2) is a redox-sensitive transcription factor that prevents oxidative stress by regulating cytoprotective genes, including NAD(P)H quinone dehydrogenase 1 (NQO1), heme oxygenase 1 (HO-1) and glutamate-cysteine ligase [ 14 ]. It is worth noting that it is reported that after feeding a high-fat diet, NRF2 inhibits lipid accumulation and oxidative stress in the liver tissue of mice by inhibiting lipogenesis and cholesterol production signaling pathways [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study reported that LPS treatment increases Mirt2 expression in macrophages through interactions with p38‐Stat1 and interferon‐Stat1 pathways, and identifies lncRNA Mirt2 as a negative feedback regulator of excessive inflammation. 13 Moreover, Bai et al 18 indicated that LPS suppresses Mirt2 expression and overexpression of Mirt2 mitigates LPS‐induced inflammatory damages in HK‐2 cells. Similarly, Li et al 19 found that lncRNA Mirt2 level is upregulated in LPS‐stimulated PC12 cells and serum samples derived from spinal cord injury patients, and overexpression of lncRNA Mirt2 protects PC12 cells from LPS‐induced injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Mirt2, termed as myocardial infarction‐associated transcript 2, is a newfound lncRNA with the activity of anti‐inflammatory. 57 Mirt2 decreased in the livers of obese mice, revealing that mirt2 was involved in NAFLD. 58 Liver‐specific mirt2 overexpression improved hepatic glucose tolerance and IR, and alleviated lipid deposition in HFD mice; meanwhile, upregulation of mirt2 improved liver function in obese mice.…”
Section: Lncrnas Involved In the Regulation Of Nafldmentioning
confidence: 91%
“…Mirt2, termed as myocardial infarction‐associated transcript 2, is a newfound lncRNA with the activity of anti‐inflammatory 57 . Mirt2 decreased in the livers of obese mice, revealing that mirt2 was involved in NAFLD 58 .…”
Section: Lncrnas Involved In the Regulation Of Nafldmentioning
confidence: 99%